INTRODUCTION TO VARIOGRAMS: Concepts, Tools, And Methods In Geostatistics: ISBN 978-630-95064-0-5 - Labbaci, Yasser (Technium Books, 2025)
The book: INTRODUCTION TO VARIOGRAMS: Concepts, Tools, And Methods In Geostatistics is published in Technium. Dr. LABBACI Yasser Researcher in Civil Engineering University of Bechar- Tahri Mohamed Department of Civil and Hydraulic Engineering LMS Laboratory (Laboratoire Mécanique des Structures) Email: Labbaci.yasser@univ-bechar.dz Bechar, Algeria December 2025